Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T20:13:48+01:00
-3x + 2y = 10
2( x -2y) + 3x = -6

-3x + 2y = 10
2x - 4y + 3x = -6


-3x + 2y = 10 / *2
5x - 4y = -6

-6x + 4y = 20
5x - 4y = -6
___________________
-6x + 4y + 5x - 4y =20 - 6
-x= 14 / *(-1)
x= - 14

x= - 14
-3x + 2y = 10

x= - 14
-3* (-14) + 2y = 10

x= - 14
42 + 2y =10

x= - 14
2y= -32 / :2

x= - 14
y= - 16

2010-03-11T20:13:58+01:00
{-3x + 2y = 10
2( x -2y) + 3x = -6
{-3x+2y=10
2x-4y+3x=-6
{-3x+2y=10 /*2
5x-4y=-6
{-6x+4y=20
5x-4y=-6
__________
-x=14 /:(-1)
x=-14

-3*(-14)+2y=10
-42+2y=10
2y=10+42
2y=52 /:2
y= 26

{x=-14
y=26
2010-03-11T20:17:18+01:00
-3x + 2y = 10
2( x -2y) + 3x = -6

-3x+2y=10
2x-4y+3x= -6

-3x+2y=10 (obie strony pomnożymy przez 2)
5x-4y= -6

-6x+4y=20
5x-4y= -6 (dodajemy stronami)


-x= 14
x= -14

-3x+2y=10 (obie strony pomnożymy przez 5)
5x-4y= -6 ((obie strony pomnożymy przez 3)

-15x+10y=50
15x-12y= -18

-2y= 32
y= -16

x= -14
y= -16
Spr.
L=-3x+2y= -3(-14)+2*(-16)= 42-32=10
L=P
L=5x-4y=5*(-14)-4*(-16)= -70 +64= -6
L=P
1 5 1